2019
DOI: 10.21203/rs.2.14078/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Prevalence, Awareness, Management and Control of Hypertension in Men and Women in Benin, West Africa: the TAHES study.

Abstract: Background Sub-Saharan Africa is facing a growing burden of non-communicable diseases, including cardiovascular diseases (CVDs), due to epidemiological transitions. Among their risk factors, hypertension is a major determinant of CVDs, but the prevalence and level of awareness and management of this condition are poorly studied in African populations. The aim of this study was to determine the prevalence of hypertension and identify its associated risk factors as well as the awareness and management of this co… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…This study's prevalence of hypertension (35.5%) is similar to other community-based studies in SSA [42][43][44]. This prevalence of hypertension was identical to the previous WHO STEPS survey in 2009 that reported 37% in males and 33% in females [22].…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 87%
“…This study's prevalence of hypertension (35.5%) is similar to other community-based studies in SSA [42][43][44]. This prevalence of hypertension was identical to the previous WHO STEPS survey in 2009 that reported 37% in males and 33% in females [22].…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 87%
“…Additional studies have been carried out in 2015 on 1777 people aged over 25 years in the population of Tanvè, a rural area 150 km north of Cotonou, and on 717 people aged 18-64 years in the Atlantic region of Benin. These studies showed a prevalence of hypertension of 32.9% in the Tanvè population and 33.9% in the Atlantic region (Desormais et al, 2019;Houssou et al, 2020). It is estimated that 60-90% of the general African population uses folk medicine in the management of diseases especially when life-long medication is required such as in the case of hypertension (Balogun and Ashafa, 2019), and also due to the easier availability and the lower cost compared to conventional medicines (Houngbeme et al, 2014;Lawson et al, 2016;Nunes et al, 2015;Sen and Chakraborty, 2017;Yuan et al, 2016).…”
Section: Introductionmentioning
confidence: 98%